Ответы и объяснения

2013-05-12T17:00:11+00:00

74.

 

x^2+6x=0

x(x+6)=0

x=0    

x+6=0

x=-6

 

 

75.

3x^2-27=0

3x(x-9)=0

3x=0

x=0

x-9=0

x=9

 

77.

 

6x^2-13x-15=0

 

D=(-13)^2-4*6*(-15)=169+360=529

x1=13-23:12=-5/6

x2=13+23:12=3

2013-05-12T17:05:13+00:00

74(а)

 

x2+6x=0

x(x+6)=0

x=0 или х+6=0

                     х=-6

 

75 (а)

3х2-27=0

3х(х-9)=0

3х=0  или х-9=0

  х=0             х=9

 

77 (а)

6х2-13х-15=0

D=132-4*6*(-15)=169+360=529 (232)

 

x1=(23+13)/12=3

x2=(23-13)/12=10/12=5/6